The production of subjectivity : Marx and philosophy - Read, Jason (Brill, 2022)
"Louis Althusser argued that Marx initiated a transformation of philosophy, a new way of doing philosophy. This book follows that provocation to examine the way in which central Marxist concepts and problems from primitive accumulation to real abstraction animate and inform philosophers from Theodor Adorno to Paolo Virno. While also examining the way in which reading Marx casts new light on such philosophers as Spinoza. At the centre of this transformation is the production of subjectivity, the manner in which relations of production produces ways of thinking and living"-- Provided by publisher.
Keywords: Marx, Karl, -- 1818-1883.; Marx, Karl, -- 1818-1883; Philosophy, Marxist.; Philosophy, Modern.; Subjectivity.; Philosophy, European.; Philosophie européenne.; Philosophie marxiste.; Philosophy, European; Subjectivity; Criticism, interpretation, etc.